Exercise training upregulates intracellular nicotinamide phosphoribosyltransferase expression in humans: a systematic review with meta-analysis - Sun, Xu; Su, Lide; Bu, Te; Zhang, Yang (Frontiers in Public Health, 2023)
Objective: Aging is associated with decreased nicotinamide adenine dinucleotide (NAD) levels, which in turn cause dysfunctional mitochondria and indirectly affect a myriad of diseases. Intracellular nicotinamide phosphoribosyltransferase (iNAMPT) serves as a central rate-limiting enzyme in NAD synthesis, making it an indispensable health mediator. This meta-analysis examined the effect of exercise training on the expression of iNAMPT in humans. Methods: We searched PubMed, Scopus, ClinicalTrials.gov, and the International Clinical Trials Registry Platform for studies published between the inception of the database and July 5, 2023. Using the common-effect model, evidence for the change in iNAMPT following exercise training was synthesized as Cohen’s d. Results: The search yielded five eligible studies. The overall effect size is 0.81, with a 95% confidence interval of 0.55 to 1.07. Therefore, a random adult will have a 71.7% probability that iNAMPT will be up-regulated following exercise training. In general, exercise training resulted in a 1.46-fold increase in iNAMPT. Our probability statistics indicate that subgroups of interest may differ practically. Specifically, there is a 79.3% probability of increased iNAMPT in men, compared to a 69.0% probability in the overall population; young adults have a 75.6% probability of having an increased iNAMPT, whereas aged adults have a 68.7% probability; and, iNAMPT has a 75.1% probability increase after aerobic exercise and a 66.4% probability increase after resistance exercise. Conclusions: Exercise training is effective for increasing iNAMPT levels in skeletal muscles. This essential enzyme regulates not only cellular energetics but also healthspan. Therefore, exercise should be promoted as a natural slow-aging lifestyle.